Composición y amplitud de la dieta del águila real en Chihuahua, México - Bravo, M. G.; Mireles, C.; Zúñiga, J.; Carreón, E. (Instituto de Ecología, A.C., 2015)
We assessed golden eagle (Aquila chrysaetos canadensis) diet and breadth composition during the breeding season 2010 in Chihuahua state, Mexico. We collected old and fresh prey remains and observed prey delivery in active territories. Diet was diverse and composedof small mammals, mainly, but includes birds and reptiles as well. Hares and rabbits were the most important in terms of relativeabundance and biomass.